The Relationship between Physical Activity and Cholesterol Levels in the Community in the Kalibaru Kulon Health Center Working Area - Sitti Syarifah; Sasmiyanto; Mohammad Ali Hamid (Penerbit Hellow Pustaka, 2024)
The number of degenerative diseases is increasing, one of which is diseases related to cholesterol. Cholesterol levels in the blood are related to physical activity, the more physical activity you do every day, the greater your daily energy expenditure, resulting in a reduction in cholesterol levels in the body. So, it is important to know the relationship between physical activity and cholesterol levels in the body. Quantitative research with a cross-sectional approach. The population in this study were all people who had had their cholesterol checked in the Kalibaru Kulon Community Health Center working area. The total population in this research was 177 people. and a sample of 44 people was taken using simple random sampling techniques. The statistical test between physical activity and cholesterol levels measured using Spearman rho with α = 0.05 resulted in p value = 0.000, and r = -0.764, meaning there is a relationship between physical activity and cholesterol levels. The suggestion of this research is that health institutions are advised to provide education related to increasing physical activity in order to reduce cholesterol levels.